PENGARUH PENAMBAHAN TAPAI SINGKONG TERHADAP SIFAT ORGANOLEPTIK SAMBAL TEMPOYAK - Mukmin -; Lina Widawati; Siska Apriyani (UNIVED Press, Universitas Dehasen Bengkulu, 2014)
Tempoyak is a durian processed foods obtained by simple fermentation , the shape of the pulp of durian flesh with a sour taste. Tempoyak made with the addition of as much as 1-5 % salt into the flesh of the fruit pieces which are then brooded for 3-4 days. This study aims to determine the level of consumer preference towards tempoyak sauce with the addition of cassava tapai. The method used in making sauce with the addition of cassava tapai tempoyak, namely by processing cassava into tempoyak with tapai tempoyak sauce. The treatment in this study is the composition variation tapai cassava ( tempoyak 500 grams : 0 grams tapai cassava , tempoyak 450 grams : 50 grams of cassava and tempoyak tapai 400 grams : 100 grams tapai cassava ). The analysis used was the analysis of organoleptic parameters premises color, flavor, and aroma of chili tempoyak tested against the 20 panelists. The results of the analysis conducted stated that based on the parameters of color, showing significant difference between the three samples . Where consumers prefer chili tempoyak with the addition of 0 grams and 50 grams of cassava tapai. Based on the parameters of taste , showed no significant difference among the three samples. Based on the parameters of aroma , showing significant difference between the three samples. Where consumers prefer chili tempoyak with the addition of 50 grams and 100 grams of cassava tapai.Keywords : Tempoyak , tapai cassava , chilli tempoyak